Trends in Direct Measures of Job Skill Requirements - Michael J. Handel (Levy Economics Institute of Bard College, 2000)
It is commonly assumed that jobs in the United Sates require ever greater levels of skill and, more strongly, that this trend is accelerating as a result of the diffusion of information technology. This has led to substantial concern over the possibility of a growing mismatch between the skills workers possess and the skills employers demand, reflected in debates over the need for education reform and the causes of the growth in earnings inequality. However, efforts to measure trends have been hampered by the lack of direct measures of job skill requirements. This paper uses previously unexamined measures from the quality of Employment Surveys and the Panel Study of Income Dynamics to examine trends in job education and training requirements and provide a validation tool for skill measures in the Dictionary of Occupational Titles, whose quality has long been subject to question. Results indicate that job skill requirements have increased steadily from the 1970s through the 1990s but that there has been no acceleration in recent years that might explain the growth in earnings inequality. There has also been no dramatic change in the number of workers who are undereducated. These results reinforce the conclusions of earlier work that reports of a growing skills mismatch are likely overdrawn.
Keywords: 330